DESIGN AND IMPLEMENTATION OF INVENTORY INFORMATION SYSTEM IN PUTRA MARIYO TRADING BUSINESS - Harisnur, Alvian; Gunawan, Dedi (LPPM Nusa Mandiri, 2022)
Technological advancement in information technology applications allows the data recording process to become easier. Putra Mariyo Trading Business is a business institution that sells wood as a building material in various types and sizes. Data processing of incoming and outgoing goods in this business is performed only by writing goods data into a specific book. Consequently, some problems such as the loss of data and miss calculation in processing transactions usually occur. Therefore, in this research, we design a system to address the problems. The system is developed by following the Waterfall software development method. To build the system, we opt to use PHP programming language, CodeIgniter framework, and MySQL as the database server. To determine system reliability, this information system testing uses black box testing which focuses on the functional requirements of the system. To evaluate the performance of the system two testing steps i.e., black-box testing and System Usability Scales (SUS) are adopted. Black-box testing results show that the error percentage of our system is 0%. The SUS testing is conducted to obtain responses from users and the SUS score obtained is 70.1 indicating that the system is at the